Gorontalo State University Medical Students Perspective On Female Genital Mutilation/ Cutting (Fgm/C) - Maimun Ihsan; Novianty Djafri; Isman Yusuf (Global Scientific Publishing, 2023)
Female Genital Mutilation/Cutting (FGM/C) from a health perspective Cutting or damaging healthy genital tissue has been proven to have no benefits, but on the contrary, FGM/C is a painful and traumatic procedure that disrupts the body's natural functions. Considering that Gorontalo is a strong region in preserving FGM/C practices, it is hoped that policies can be initiated at various Medical Faculties, Midwifery Faculties and Midwifery Schools to include a curriculum regarding FGM/C and its complications as a local content course. The quantitative method used is. The instrument is a questionnaire distributed via Google form. held in November 2023 at the medical faculty of Gorontalo State University
Keywords: Female Genital Mutilation; Cutting; perspective